2006
DOI: 10.1007/s11229-006-9036-x
|View full text |Cite
|
Sign up to set email alerts
|

A Semantics for Means-end Relations

Abstract: There has been considerable work on practical reasoning in artificial intelligence and also in philosophy. Typically, such reasoning includes premises regarding means-end relations. A clear semantics for such relations is needed in order to evaluate proposed syllogisms. In this paper, we provide a formal semantics for means-end relations, in particular for necessary and sufficient means-end relations. Our semantics includes a non-monotonic conditional operator, so that related practical reasoning is naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Meanwhile, the third category of semantic relations, namely polysemy as stated by Allwood (2003), Biederman (2017), Hjørland (2007, Hughes et al(2007), Jackendoff (2006), Jackson (2014) was not found in the naming places in the West Coast of Sumatra. This finding supports that the West coast of Sumatra in the four provinces construct names from the same word or are synonymous to have the meaning.…”
Section: Online Issn 2928-3936mentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, the third category of semantic relations, namely polysemy as stated by Allwood (2003), Biederman (2017), Hjørland (2007, Hughes et al(2007), Jackendoff (2006), Jackson (2014) was not found in the naming places in the West Coast of Sumatra. This finding supports that the West coast of Sumatra in the four provinces construct names from the same word or are synonymous to have the meaning.…”
Section: Online Issn 2928-3936mentioning
confidence: 95%
“…In line with Pateda, (Gorys Keraf, 2009a) states that what is meant by lexical structure are the various semantic relations contained in the word. Allwood (2003), Biederman (2017), Hjørland (2007, Hughes et al (2007), Jackendoff (2006), Jackson (2014) categorize the meaning relation into three synonym meaning relations, antithymic meaning relations, and polysemic meaning relations. These three semantic relations are basically found in naming places.…”
Section: Introductionmentioning
confidence: 99%
“…There, instruments were used, not as a means for reducing deontic operators, but as a refinement for talking about instruments that are obligatory or forbidden. An alternative approach is that of BDI (Belief-Desire-Intention) logic see Meyer et al (2015) due to its connection to means-end reasoning (see also Hughes et al (2007)). However, such logics do not fully accommodate the required distinction between actions and outcomes as in van Berkel and Pascucci (2018).…”
Section: Related Logicsmentioning
confidence: 99%
“…Concerning these matters, the philosophy of technology arguably can profi t much from what goes on in logic and, increasingly, technical off-spring areas like artifi cial intelligence, where many 'logics of action' have been developed. Examples of what introducing logical expertise to well-known problem areas in technology has to offer are the analysis of means-ends reasoning (Hughes et al 2007 ) and of the assignment of responsibility in situations where 'many hands' contribute to an end situation (de Lima and Royakkers 2015 ).…”
Section: The Concept Of Designmentioning
confidence: 99%